The Influence Of Capital Structure And Dividend Policy On Company Value In Healthcare Sector Of Companies Listed On The Indonesian Stock Exchange - Desty Saputri; Mariaty Ibrahim (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to analyze the effect of capital structure measured by the Long-term Debt to Equity Ratio (LDER) on company value, the effect of capital structure measured by the Debt to Equity Ratio (DER) on company value, the effect of dividend policy measured by the Dividend Yield Ratio (DYR) on company value, and the effect of dividend policy measured by the Dividend Payout Ratio (DPR) on company value in healthcare sector of companies listed on the Indonesian Stock Exchange. This research used descriptive quantitative method. The population in this study was 35 healthcare sectors of companies listed on the Indonesian Stock Exchange. Using the purposive sampling method, a sample of 10 companies was obtained over 4 years so that the total sample was 40. The data used in this research is secondary data in the form of annual reports and company financial reports, and the data was analyze using SPSS version 25. The results of this study show that capital structure measured by the Long-term Debt to Equity Ratio (LDER), capital structure measured by the Debt-to-Equity Ratio (DER), and dividend policy measured by the Dividend Yield Ratio (DYR) have a negative significant effect on company value, while dividend policy measured by the Dividend Payout Ratio (DPR) has a positive significant effect on company value